Brainbow: New Resources and Emerging Biological Applications for Multicolor Genetic Labeling and Analysis. Issue 2 (2nd February 2015) - Weissman, Tamily A; Pan, Y Albert
Abstract: Brainbow is a genetic cell-labeling technique where hundreds of different hues can be generated by stochastic and combinatorial expression of a few spectrally distinct fluorescent proteins. Unique color profiles can be used as cellular identification tags for multiple applications such as tracing axons through the nervous system, following individual cells during development, or analyzing cell lineage. In recent years, Brainbow and other combinatorial expression strategies have expanded from the mouse nervous system to other model organisms and a wide variety of tissues. Particularly exciting is the application of Brainbow in lineage tracing, where this technique has been instrumental in parsing out complex cellular relationships during organogenesis. Here we review recent findings, new technical improvements, and exciting potential genetic and genomic applications for harnessing this colorful technique in anatomical, developmental, and genetic studies.